THE ROLE OF NGOs IN LIBERAL PEACE ATTEMPTS - Made Fitri Padmi (GLOBAL INSIGHT JOURNAL, 2017)
Abstract The post-Cold War era has seen the expansion of involvement by non-state actors in the spreading of liberal peace principles. NGOs are one of the non-state actors which have been actively advocating the value of liberal peace. This paper would like to analyze the role of NGOs in spreading the value of peace throughout the world. The paper began in the concern of the rising number of civilian casualties during armed conflicts. This paper examines liberal peace as a pathway to global improvement and as a source of sustainable peace. NGOs take the grassroots approach to views of conflict, peacebuilding, development, and promoting liberal values by involving the local community and local authority. NGOs emerge to fill the gap of liberal peacebuilding projects that cannot be reached by the state. The legally-mandated neutrality of NGOs gives them more access to build peace as they are seen as less threatening parties. Despite the criticism of NGOs as the vehicle of state interests, NGOs are able to be good partners for the state to establish liberal peace. The case study of NGO involvement in Afghanistan describes how NGOs work to protect human rights, empower communities, and other humanitarian projects. Keywords: NGOs, liberal peace, democracy, peacebuilding Abstrak Era pasca-Perang Dingin telah menjadi saksi bagi perluasan keterlibatan aktor-aktor non-negara dalam penyebaran prinsip-prinsip perdamaian liberal. NGO adalah salah satu aktor non-negara yang telah secara aktif menganjurkan nilai perdamaian liberal. Tulisan ini ingin menganalisis peran NGO dalam menyebarkan nilai perdamaian di seluruh dunia. Tulisan ini mulai menjadi perhatian meningkatnya jumlah korban sipil selama konflik bersenjata. Penelitian ini mengkaji perdamaian liberal sebagai jalur menuju perbaikan global dan sebagai sumber perdamaian yang berkelanjutan. NGO mengambil pendekatan akar rumput untuk melihat konflik, pembangunan perdamaian, pembangunan, dan mempromosikan nilai-nilai liberal dengan melibatkan masyarakat lokal dan pemerintah daerah. NGO muncul untuk mengisi kesenjangan proyek pembangunan perdamaian liberal yang tidak dapat dicapai oleh negara. Azas netralitas yang diamanatkan pada NGO memberi mereka lebih banyak akses untuk membangun perdamaian karena dipandang sebagai pihak yang kurang mengancam. Meskipun ada kritik terhadap NGO sebagai alat bagi kepentingan negara, NGO dapat menjadi mitra yang baik bagi negara untuk mewujudkan perdamaian liberal. Studi kasus keterlibatan NGO di Afghanistan menggambarkan bagaimana NGO bekerja untuk melindungi hak asasi manusia, memberdayakan masyarakat, dan proyek kemanusiaan lainnya. Kata kunci: NGO, perdamaian liberal, demokrasi, peacebuilding